Sustainable management (SM) guide in GBI interiors design project tools - Yaman, Rostam; Adnan, Hamimah; Ismail, Farrah Zuhaira; Ahmad, Noraini (Asian Research Publishing Network (ARPN), 2015)
The paper aims to study and measure the applicability of GBI tools for interior design project. The studies specifically focus on one of the GBI Tools assessment criteria which is Sustainable Planning and Management (SM). The SM criteria is chosen as assessment sampling as it make out the main point scoring system in GBI for Interiors Tools. The pilot study is to measure and benchmarked the standards and applicability of the tools. The methodology used is on-site observation and GBIAP score result. Outcome from the research suggest framework criteria are highly applicable and meet Malaysia Green Building Confederation (MGBC) standards. Based on selected related study, it is imperative to apply and highly encouraging to implement green design in interior design as it hold a significant sustainable awareness and marketable values.